An Evaluation of the Neural Activity Marker c-Fos in the Brain and Gut Following an Acute Dose of the Probios Isolate Enterococcus Faecium. (7th June 2021) - Bauer, Ella; Shoeman, Allyse; Frese, Alexis; Clark, Peter
Abstract: Objectives: Gut microbes, including probiotics, can exert a wide range of effects on the host, such as influencing gastrointestinal function and, in some cases, brain function and behavior. Although long-term exposure to certain probiotics have also been shown to alter brain function via vagal communication routes, it is possible that probiotics may influence the brain more acutely, such as shortly after administration. Indeed, gastrointestinal stimuli can activate vagal-dependent brain reward pathways within minutes of induction. Therefore, this study aimed to examine the short-term effects of acute probiotic exposure on neural activity in the brain and gut. Methods: CF-1 mice were divided into three groups: probiotic (10 9 CFUs Enterococcus faecium in 200 ul PBS), gavage control (200 ul PBS), control groups (handling only). These groups were further divided into 3 subgroups to evaluate the temporal effects of acute probiotic administration at 3, 5, and 7 hours after a single dose of probiotic. c-Fos immunohistochemistry was used as a marker of neural activity in multiple regions of the brain and gut suggested to be affected by probiotics. Results: Preliminary findings suggest that c-Fos positive cell density in the dentate gyrus of the hippocampus and ventral tegmental area were unaffected by acute administration of E. faecium. Data collection of c-Fos density is underway in other brain areas (i.e., parabrachial nucleus, bed nucleus of the stria terminalis, caudate putamen, pontine nucleus, and solitary nucleus tract) as well as the intestines (i.e., duodenum, jejunum, ileum, cecum, proximal and distal colon). Conclusions: While preliminary evidence indicates that the dentate gyrus and ventral tegmental area were unaffected within the initial hours after a single dose of E. faecium, many brain and gut areas remain to be analyzed. Together, these data may collectively provide insight into the immediate effects of probiotics on gut and brain activity. Funding Sources: This work was supported by Iowa State University start-up funds.